O regional na comunicação publicitária : o posicionamento identitário da marca Polar - Gambin, Aline (My University, 2015)
Guided by research in the field of Cognitive Linguistics and Social Communication, this thesis, of the interdisciplinary nature, aims to answer the following question: What does the Polar beer case reveal about the conceptualization of the REGIONAL through advertising discourse by employing multimodal expressions of metaphorical and metonymic character? The hypothesis that guides this research, in relation to the formulated problem, is that the multimodal language exploits a stereotypical construction of gaúcho in the production of publicity material of the Polar brand. Specifically, the aim is to identify how the GAUCHO cultural model is used by multimodal language to position the Polar brand and thereby create emotional connections with consumers. In order to corroborate the hypothesis, the case of the Polar brand has been assembled, making use of the method of case study, forming corpora consisting of three corpus categories, namely: three pieces of print media advertising, three pieces of digital media and three videos. As a theoretical framework to support these analyses Tavares (1998), Martins (1999, 2006), Pine (1996), Aaker (2001), Aaker and Joachimsthaler (2002), Torres (2010), Gobé (2002) have been elected for the study of emotional impressions. Lakoff (1980, 1987), Forceville and Urios Aparisi (2009), Forceville (1996, 2009), Koller (2009) and Feltes (2007) have been elected for the study of conceptual metaphor and metonymy. Holland and Quinn (1987), D'Andrade (1987) Quinn (1987, 1997), Strauss and Quinn (1997), in their turn, have guided the study of cultural models. The analysis of corpora shows that (a) the media pieces make wide use of the multimodality of language, with emphasis on verbal and nonverbal metaphors and metonymies; and (b) the media producers operate on a ad hoc REGIONAL GAUCHO cultural model, producing a blended representation by conceptual elements from different regions of the state of Rio Grande do Sul, built for the achievement of the specific purposes of their advertisement campaigns.
Norteada pelas pesquisas no domínio da Linguística Cognitiva e da Comunicação Social, esta dissertação, de cunho interdisciplinar, objetiva responder ao seguinte questionamento: o que o case da cerveja Polar revela sobre a conceptualização de REGIONAL, através do discurso publicitário e pelo emprego de expressões multimodais de caráter metafórico e metonímico? A proposição que orienta essa pesquisa, na relação com o problema formulado, é que a linguagem multimodal explora uma construção estereotipada de gaúcho na produção das peças publicitárias da marca Polar. Especificamente, visa-se identificar como o modelo cultural do GAÚCHO é utilizado através da linguagem multimodal para posicionar a marca Polar e, com isso, criar vínculos emocionais com os consumidores. Para a corroboração da proposição, montou-se o case da marca Polar servindo-se do método de estudo de caso, formando-se corpora constituídos por três categorias de corpus, quais sejam: três peças publicitárias de mídia impressa, três peças de mídia digital e três vídeos. Como referencial teórico para sustentar essas análises, optou-se por Tavares (1998), Martins (1999; 2006), Pinho (1996), Aaker (2001), Aaker e Joachimsthaler (2002), Torres (2010) e Gobé (2002) para o estudo das marcas emocionais; Lakoff (1980; 1987), Forceville e Urios Aparisi (2009), Forceville (1996; 2009), Koller (2009) e Feltes (2007) para o estudo de metáforas e metonímias conceptuais; e Holland e Quinn (1987), D’Andrade (1987), Quinn (1987; 1997), Strauss e Quinn (1997) para o estudo de modelos culturais. A análise dos corpora revela que (a) as peças midiáticas servem-se amplamente da multimodalidade da linguagem, com ênfase em metáforas e metonímias verbais e não verbais; e (b) os produtores das mídias operam sobre um modelo cultural REGIONAL GAÚCHO de caráter ad hoc, produzindo uma representação conceptual mesclada por elementos de diferentes regiões do estado do Rio Grande do Sul, construída para a consecução dos propósitos específicos de suas campanhas de propaganda.
Keywords: Publicidade - Regionalismos - Rio Grande do Sul; Marca registrada; Publicity - Provincialisms - Rio Grande do Sul (Brazil); Trademarks